Effect of Genotypes and Row Spacing on Growth and Yield of Sesame (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: Genotype; row spacing; sesame; crop growth rate; relative growth rate; yield Bangladesh j. genet. biotechnol. 6 (1&2): 5-10, 2005 (June & December)